Primary Alevi institutions and Alevi-Sunni encounters under the urban conditions - Yıldırım, Olcay. (Thesis (M.A.)-Bogazici University.Atatürk Institute for Modern Turkish History, 2009., 2009)
This study examines the experiences, opinions and feelings of the members of the Alevi community who are currently living in the urban centers concerning the two dramatic consequences of their migration into the urban centers as of the 1950s. These two dramatic consequences are the transformation of the most primary rituals and institutions which form the basis of the socio-religious organization of the traditional Alevism, under the urban conditions as opposed to the rural context, and the unique increase in the possibility of the Alevi-Sunni encounters within the urban context compared to the rural conditions. These two consequences are dealt with not only as mere results of Alevis’ migration from the rural parts of Turkey into the urban centers, but within a much broader context of the transformation of their traditionally closed, marginal and secrecy-based character as a community into a different one ready to open up to the wider society. This study is based on the existing literature both related to the closed, marginal and secrecy-based character of the traditional Alevi community and their opening into the wider society, as well as on the face-to-face interviews conducted with nineteen members of the Alevi community living in the urban centers. The conclusions reached were that while most of the informants were discontented with the weakening of the primary rituals and institutions of the traditional Alevism under the urban conditions, all of them considered the unique increase in the possibility of Alevi-Sunni encounters within the urban setting as an opportunity to eliminate the prejudices of the Sunni community against the Alevi which were based on hearsay.
Keywords: Shiites -- Turkey.; Sunnites.